2002
DOI: 10.1006/qres.2002.2339
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Timing and Duration of the Last Interglacial Period from High-Precision Uranium-Series Ages of Corals on Tectonically Stable Coastlines

Abstract: The last interglacial period has a timing and duration that can be estimated from U-series dating of emergent, coral-bearing deposits on tectonically stable coastlines. High-precision dating from Bermuda, the Bahamas, Hawaii, and Australia suggests that the last interglacial period had a sea level at least as high as present from ∼128,000 to 116,000 yr B.P. Sea level reached a near-present level more quickly after the close of the penultimate glacial period than at the close of the last glacial period and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 20 publications
(39 reference statements)
5
44
0
Order By: Relevance
“…But unfortunately there is no universal agreement on its precise age or the elevation of its sea-level, and ages range from ∼132 to 116 ka. These point to a longer interglacial than predicted by orbital theory (Muhs, 2002;Muhs and Szabo, 1994;Stein et al, 1993). Thus, the global complexity of the climate system may have resulted in a long sea-level response during the last interglacial , with different responses in earlier ones (Siddall et al, 2007).…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…But unfortunately there is no universal agreement on its precise age or the elevation of its sea-level, and ages range from ∼132 to 116 ka. These point to a longer interglacial than predicted by orbital theory (Muhs, 2002;Muhs and Szabo, 1994;Stein et al, 1993). Thus, the global complexity of the climate system may have resulted in a long sea-level response during the last interglacial , with different responses in earlier ones (Siddall et al, 2007).…”
Section: Methodsmentioning
confidence: 83%
“…Potter and Lambeck (2003) have also suggested that MIS 5.1 marine deposits above sea-level on the US Atlantic Coastal Plain (Wehmiller et al, 2008) result from glacio-hydro-isostasy. Yet Muhs et al (2002) suggest that such a high sea-level should be expected, given the complete deglaciation of the Laurentide Ice Sheet at a time when Baffin Island was warmer than the Holocene Wolfe et al, 2000). Summer temperatures, higher than present, in northern Fennoscandia during MIS 5.1 also suggest complete deglaciation of the Fennoscandian ice sheet (Valiranta et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The difference between the planktonic and the benthonic datum is expectable in the tropics where sea-surface temperatures were relatively high during the periods of ice growth (Kukla et al, 2002a). An indirect age assignment of Termination II comes from interglacial coral reefs (Muhs, 2002). The highest eustatic sea level and, consequently, the lowest global ice volume have been dated to ca.…”
Section: Deep Ocean Stratigraphymentioning
confidence: 99%
“…(4) There is a broad-scale consensus over the timing and the elevation of the Last Interglacial (MIS 5e) sea-level. During this time period, sea-level was several meters higher than that of today (w4 AE 2 m apsl) and the start of MIS 5e high stand has been dated to w128 ka BP in tectonically stable sites (Chen et al, 1991;Stirling et al, 1995Stirling et al, and, 1998McCulloch and Esat, 2000;Muhs, 2002;Blanchon et al, 2009). Therefore, in tectonically uplifting areas, in order to determine vertical tectonic uplift rates, the elevation and the age of MIS 5e coastlines are used.…”
Section: Dogan Et Al Present Their Esr and U/th Dating Results Of Thmentioning
confidence: 99%